A simulation-based framework for a mapping tool that assesses the energy performance of green roofs - Kokogiannakis, Georgios; Darkwa, Jo (2012)
This paper presents a framework for the development of a GIS open source mapping tool that aims to disseminate a database with results of detailed simulations in order to assess in a quick and easy way the energy performance of green roof designs across a range of Chinese climates. Detailed simulation results for heating and cooling loads are obtained from the EnergyPlus simulation tool. The study covers 12264 configurations by varying model parameters such as climate, glazing type, roof insulation, soil and plant characteristics, etc. It was found that green roofs can offer significant energy savings if they are applied on roofs without insulation but only limited energy savings where heavy insulation on the roof is also applied. Quick comparisons across a large range of roof characteristics could be easily made with the implementation of the GIS map tool and the design of green roof that fits the specific climate could be optimised without the knowledge of a detailed building energy simulation tool. The critical parameters that affect the green roof’s performance are also highlighted.